The Effect of the Pentagram Strategy on Achievement Among Fifth Year Middle School Students in Chemistry (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to identify the effect of the Pentagram strategy on achievement among fifth-year middle school students in chemistry. As the experiment began on Sunday (11/29/2020), and ended on Wednesday (2/17/2021), The research sample was randomly selected Which was represented by (Al-Huda Preparatory for Girls) affiliated to the Baghdad Education Directorate / Al-Rusafa II, as the sample size reached (50) students, and the experimental design with partial control was chosen for the two equivalent groups (experimental and control). The experimental number is (25) students taught according to the strategy of the Pentagon, and a control number (25) students are taught according to the usual method. The two research groups were rewarded statistically in some variables (intelligence test, previous achievement, previous information test,). (216) Behavioral objectives for the educational material, which included the first four chapters (first, second, third, fourth) of the fifth-grade chemistry textbook (biological), the research tool, represented by the achievement test, was built. The results were statistically treated and showed: The experimental group students who studied according to the Pentagram strategy outperformed the control group students who studied according to the usual method of achievement test.